(untitled) (Eurasian Research Bulletin, 2022)
This article considers the types of creating an exercises system of aimed at studying a define topic of the lexical aspect of the language. The main objective of the method is to strengthen and develop knowledge in the process of practical activity. All of the following types of exercises can be used at teaching English homonyms, however, it is necessary to distribute their quantitative and qualitative ratio according to the topic being studied